(untitled) (Malaysian Journal of Civil Engineering, 2018)
Cement based materials such as concrete and mortar are widely used in construction industry. One of the drawbacks of concrete or mortar is its low tensile strength that will affect cracking. Thus, enhancing its tensile strength using short fibres is beneficial in reducing problems caused by cracks. This study highlights the effects of natural horse hair and kenaf fibres with different curing conditions on the properties of mortar. Three different curing conditions were employed namely, water curing, air curing and 7-days in water and thereafter dry curing. The mortar samples, cubes and prisms, were tested in compression and flexure at the ages of 3, 7 and 28 days. In addition, the water absorption, fibre surface and mode of failure of the samples were also recorded and analysed. The experimental results show that the inclusion of horse hair and kenaf fibres enhanced the flexural strength but reducing the workability of the mortar. The horse hair mortar recorded higher flexural and compressive strengths compared to kenaf fibre mortar. However, the effect of fibres on the compressive strength was not significant in which the control sample recorded higher compressive strength compared to horse hair and kenaf fibre mortars. In addition, the water absorption for kenaf fibre was higher than horse hair due to its porous microstructure. It was recorded also that the samples with natural horse hair and kenaf fibres failed in a ductile manner compared to control sample due to the bridging effect of the fibres that able to hold the matrix together.